Small-scale land use effects on plant communities in Mediterranean urban ecosystems - Vincenzo Baldi; Alessandro Bellino; Daniela Baldantoni (Ecological Indicators)
The spatial configuration of urban landscapes, characterized by complex mosaics of fragmented patches subjected to different land uses, shapes biodiversity and, therefore, affects ecosystem stability and functioning. The present study focuses on evaluating the small scale variations of vegetation structural and functional biodiversity in Mediterranean urban ecosystems, in relation to land use and fragmentation. For the structural biodiversity, taxa were identified at the species level, estimating their abundance through several measures (number, dry mass, Braun-Blanquet cover), whereas functional traits (biological form, chorological type, Ellenberg indices) were adopted in evaluating vegetation functional diversity. Data analysis relied on the derivation of synthetic structural and functional diversity indices, employed together with community composition and species abundances in ascertaining how land use (pathways, lawns, tree rows) and margin effect (distance from interfaces) drive the diversity of plant communities. Overall, results indicate a remarkable heterogeneity of plant communities, even at scales in the order of few meters, with land use and margin effect differentially affecting their structural and functional biodiversity. The main drivers of biodiversity appear to be a combination of anthropogenic pressures (e.g. trampling/soil sealing) and the presence/absence of canopy shading, determining higher abundances of therophytes (especially Asteraceae and Poaceae) in open and trampled spaces and a proportional increase in hemichryptophytes under canopies. Findings suggest a large leeway in enhancing biodiversity and environmental heterogeneity in urban ecosystems through sustainable land planning, focusing on the type and spatial arrangement of green areas.